Absence and Presence of Human Interaction: The Relationship Between Loneliness and Empathy - Hu, Tingyun; Zheng, Xi; Huang, Miner (Frontiers in Psychology, 2020)
Loneliness is the negative experience of a discrepancy between the desired and actual personal network of relationships. Whereas past work has focused on the effect of loneliness on prosocial behaviors, the present research addressed the gap by exploring the effect of loneliness on empathy. Empathy is an emotional reaction of sharing in others’ internal experiences. We adopted a new paradigm-empathy selection task, which uses free choices to assess the desire to empathize. Participants made a series of binary choices, selecting situations that instructed them to empathize or objectively describe. Results from two studies showed that compared to nonlonely, lonely people were more likely to choose positive empathy but to avoid negative empathy. The pattern occurs because lonely people perceived higher (versus lower) social support in the positive (versus negative) empathy tasks. Moreover, empathy served to be an adaptive emotion regulation strategy developed by lonely people to reduce their loneliness effectively. This research has both theoretical contributions to prosocial behavior literature and practical implications for loneliness intervention.